An assessment of tree biodiversity and carbon stocks in mangrove forests, Langsa City, Aceh, Indonesia. Issue 1 (November 2021) - Maimunah, Siti; Hanafi, Ilham; Subhan; Anhar, Ashabul; Samek, Jay H.
Abstract: Mangrove forests are a unique coastal ecosystem with trees adapted to a constantly fluctuating and sometimes extreme physical environment. Mangrove forests provide important ecosystem services that benefit local people and all of us in terms of climate regulation through the storage of greenhouse gasses in biomass. This research reports carbon stock, wood volume, tree density, and biodiversity indices for two mangrove forest areas in Langsa City Regency, Aceh Province, Indonesia. The two sites represent and inland area and an ocean-exposed area within a large mangrove forest ecosystem complex. The results of the analysis show that these two tracts are quite similar in terms of carbon stock and biodiversity even though they occupy different locations within the larger tract of mangrove habitat. The study confirms these are healthy forest areas with relatively high carbon stocks.